Composition of the Process of Long-Term Preparation of Athletes and Their Relationship with Their Physical Development - Sardorbek, Talibjonov (Researchparks Publishing, 2023)
Relevance of the topic. Today, the process of training highly qualified athletes is a complex process that requires the practical application of scientifically based training tools and methods. It is important to take into account the nature of the sport when developing a long-term training structure. It is necessary to take into account the level of physical development and physical fitness of the athlete in the distribution of annual loads according to the types of sports.